2020
DOI: 10.3390/agriculture10030086
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Hypochlorite Treatment: The Impact on Bacteria and Endotoxin Concentrations in Drinking Water Pipes of A Pig Nursery

Abstract: Poor drinking water quality can affect pigs’ health and performance. The disinfection of water may enhance microbial water quality. In this study, bacteria and endotoxins in sodium hypochlorite-treated and -untreated water from one pig nursery were analyzed. Water samples were taken from incoming water and from compartments with treated and untreated water at the beginning and end of pipes and from nipples. The farm was visited 14 times to measure total bacteria counts and concentrations of Pseudomonas spp. an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The leachate show very high values of coliform count >1800 CFU/ml from the result obtained in Table 1. Coliform bacteria can be opportunistic pathogens and are regarded as indicator organisms for fecal contamination (Böger et al, 2020). The confirmatory test carried out in this study (Table 2) showed that the coliform present in the water sample were thermo-tolerant coliform that were both Escherichia coli, and nonE.…”
Section: Resultsmentioning
confidence: 51%
“…The leachate show very high values of coliform count >1800 CFU/ml from the result obtained in Table 1. Coliform bacteria can be opportunistic pathogens and are regarded as indicator organisms for fecal contamination (Böger et al, 2020). The confirmatory test carried out in this study (Table 2) showed that the coliform present in the water sample were thermo-tolerant coliform that were both Escherichia coli, and nonE.…”
Section: Resultsmentioning
confidence: 51%
“…Concerning biofilm formation, co-culture biofilms were chosen because interspecies interactions may influence the outcome during antibiotic or disinfectant exposure experiments when compared with monoculture approaches [ 38 , 39 , 40 ]. The well-known biofilm formers pseudomonads ( P. aeruginosa or P. fluorescens ) were used due to their frequent detection in pipes of broiler [ 17 ] or pig premises [ 18 ], as well as due to their ability to aggregate rapidly and form biofilms [ 41 ]. Additionally, a reference strain of E. coli was included in the experiments as a representative of microbes, which are not usually part of water flora but may reach pipe networks via contamination with manure and pose a health risk for animals consuming water [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The well-known biofilm formers pseudomonads ( P. aeruginosa or P. fluorescens ) were used due to their frequent detection in pipes of broiler [ 17 ] or pig premises [ 18 ], as well as due to their ability to aggregate rapidly and form biofilms [ 41 ]. Additionally, a reference strain of E. coli was included in the experiments as a representative of microbes, which are not usually part of water flora but may reach pipe networks via contamination with manure and pose a health risk for animals consuming water [ 18 ]. Based on the constant number of culturable bacteria after 7 days ( Figure 1 ), the present biofilm growth method fulfilled quality requirements in terms of repeatability as well as uniformity for both co-culture biofilms, and therefore, seemed to be adequate for studying biofilm–antibiotic confrontation at an experimental level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations